Tamanho de amostra para caracteres morfológicos e produtivos de grão-de-bico - Ortiz, Vithória Morena (2024)
Chickpea (Cicer arietinum L.) is an annual plant of indeterminate growth, being the third most cultivated legume globally. Due to its importance in consumption, research must be carried out in field experiments. In these researches, experimental planning is essential to obtain accurate results. The objectives of this work were to determine the sample size for estimating the average morphological and productive characters of chickpea cultivar BRS Cristalino and to verify whether there is variability in the sample size between characters, sowing dates and evaluation dates. In the experimental area of the Department of Plant Science at the Federal University of Santa Maria – UFSM, uniformity trials (blank experiments) were carried out in the years 2022 and 2023 with the chickpea crop. The first uniformity test was composed of 14 rows of 20 m in length spaced at 0.50 m per row and 0.06 m between plants, and the sowings of the remaining trials were composed of four rows of 5 m in length spaced at 0.50 m between rows and 0.06 m between plants, to evaluate morphological traits: plant height, number of leaves, number of nodes and number of plant branches and of productive traits: number of pods without grains, number of pods with one grain, number of pods with two grains, number of pods, number of grains, shoot mass with grains, grain mass, shoot mass without grains and harvest index. The minimum, maximum, mean, median, standard deviation, coefficient of variation, skewness and kurtosis statistics and the p-value of the Kolmogorov-Smirnov normality test were calculated. The appropriate sample size was determined to estimate the average of morphological traits on sowing and evaluation dates, and productive traits on sowing dates, for estimation errors equal to 5%, 10%, 15%, 20 %, 25% and 30%. There is variability in sample size for morphological and productive traits. 100 and 58 plants are needed to estimate the average morphological and productive traits of chickpeas with estimation errors equal to 10% and 30%, respectively.